Effect of Neurofeedback Rehabilitation on the Balance and Fall Risk of the Elderly: A Systematic Review - Ali Yalfani; Masoud Azizian; Behnam Gholami-Borujeni (تحقیقات سلامت در جامعه)
Introduction and purpose: The elderly population is increasing in most countries, and as age increases, balance disorder and fall risk become important health-related indicators. The aim of this study was a systematic review related to the effect of neurofeedback rehabilitation protocol on balance and fall risk in the elderly. Methods: In this research, a systematic library review was conducted according to the guidelines established by PRISMA. Articles were selected from the information databases of the SID, Magiran, Irandoc, SPORTDiscus, PEDro, Trip, PubMed, and Google Scholar using the following keywords: “Balance,” “Elderly,” “Rehabilitation,” “Neurofeedback training,” “Fall risk,” and “Fear of falling” in Persian and English language. Results: Following the initial review, a total of 491 articles were retrieved from various databases. Specifically, there were 14 articles from the SID database, 82 articles from the Magiran database, 19 articles from the Irandoc database, 121 articles from the Google Scholar database, 68 articles from the PubMed database, 42 articles from the SPORTDiscus database, and 17 articles from the CINAHL database. Subsequently, 7 studies were chosen for further examination. In terms of study quality, as per the National Institute of Health criteria, 3 studies were classified as high quality, 1 study as medium quality, and 3 studies as low quality. Conclusion: The current study showed that neurofeedback training using the protocol of increasing the Beta brain waves and decreasing the Theta brain waves could be more effective in improving balance and reducing the risk of falls in the elderly than balance training, somatosensory training, and physical training.